Atopy patch tests in allergological diagnostics of patients with atopic dermatitis - Czarnecka-Operacz, Magdalena (Przewodnik Lekarza/Guide for GPs, 2006)
Atopic dermatitis (AD) is an inflammatory skin disorder with increasing incidence, characterized by severe pruritus, a chronically relapsing course, clinically distinctive morphologic features and characteristic distribution of skin lesions. It is often associated with a personal or family history of atopic diseases. Although genetic factors are strongly involved in the development of the disease, various widespread factors seem to be necessary to provoke it. Such provocative factors include airborne allergens, food allergens, microbial organisms, sex hormones, stress, sweating and climate. Airborne allergens like house dust mites, plant pollen allergens, animal epithelia or moulds may be responsible for severe exacerbations of skin lesions in AD patients and there are basically two possible routes of such an influence. One route is by inhalation and the other one, which seems to be far more important, is by skin contact with environmental allergens. An increasing number of reports demonstrate that in selected patients with AD, eczematous skin lesions can be induced after epicutaneous patch testing with airborne allergens. For this procedure the term atopy patch test (APT) was proposed. This paper presents updated knowledge on APT which should be considered as a valuable tool in allergological diagnostics of AD patients. Unfortunately technical features of APT still need to be characterized and further studies are necessary before we can include these tests into the routine procedures. atopic dermatitis, airborne allergens, atopy patch tests.